APLIKASI MEDIA PEMBELAJARAN GERAKAN SHOLAT SUNNAH BERBASIS AUGMENTED REALITY - Saing, Ferdiansyah; Harfiah, Syari (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Prayers are divided into two types, obligatory prayers and sunnah prayers. Learning the Sunnah prayer movements should be trained from an early age (children). Guidance from parents and teachers is the most important way of providing learning media. So far, conventional learning in the form of books makes children bored so that creativity or interactive learning methods are needed, one of which is multimedia-based learning. One of the multimedia technologies currently developing is Augmented Reality. By utilizing Augmented Reality technology, books that have been used for learning media can be added to the Augmented Reality media. The type of research that will be carried out in this study is to create a learning media application for the Sunnah prayer movement based on Augmented Reality. This sunnah prayer learning media application can display a 3D animation along with the sunnah prayer reading options by activating the smartphone camera then detecting the marker that has been provided so that an output appears in the form of a 3D animation display along with the sunnah prayer reading options and displays the sunnah prayer reading text accompanied by audio